First checklist of centric and araphid diatoms from the benthic environments of the Gulf of Tomini, Sulawesi, Indonesia - SULASTRI ARSAD; MAŁGORZATA BĄK; FRANCISCO OMAR LÓPEZ-FUERTE; JINSOON PARK; Mateusz Rybak; ROMAIN GASTINEAU (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Arsad S, Bąk M, López-Fuerte FO, Park J, Rybak M, Gastineau R. 2026. First checklist of centric and araphid diatoms from the benthic environments of the Gulf of Tomini, Sulawesi, Indonesia. Biodiversitas 27 (5): d270510. https://doi.org/10.13057/biodiv/d270510. Sulawesi, one of the largest islands in Indonesia, includes the Gulf of Tomini, a region with diverse coastal ecosystems. However, comprehensive taxon-based checklists of benthic diatoms remain limited. The aim of this study is to present the first systematic checklist of centric and araphid marine diatoms from the benthic environment of the Gulf of Tomini, Sulawesi, documenting their occurrence across sampling sites and substrate types, and highlighting taxa with the highest cumulative counts and taxonomically uncertain taxa. Fourteen samples were collected from seven sites across the gulf from various substrates, including sediment, rocks, macroalgae, seagrass, and mangrove roots. Identification was carried out using Light Microscopy (LM) based on standard taxonomic literature. A total of 82 taxa were recorded, comprising 40 genera and 20 families; among these, 13 taxa were identified as sp., seven as cf., and four as var. The species-level uncertainty for taxa identified as sp., including Cyclophora, Thalassiosira, Cratericulifera, Opephora, Ardissonea, Dimeregramma, Neofragilaria, Rhaphoneis, Tabularia, and Talaroneis may result from the limited ultrastructural resolution of LM and the absence of comparable data in the literature. Grammatophora marina and Hyalosynedra laevigata were consistently recorded across all sampling sites and substrates. Together with Tabularia fasciculata, Cyclophora sp., Paralia longispina, and P. sulcata, these taxa represented the highest cumulative counts from all sites and substrates. This study provides baseline taxonomic information on centric and araphid diatoms for this region and establishes a foundation for future taxonomic, ecological, and diatom diversity in Indonesian coastal waters.